Strategi Bertahan Pedagang Kue Basah dalam Upaya Menghadapi Persaingan Online Shop Di Desa Sikur Kabupaten Lombok Timur - Susilawati, Susilawati; Zain, Rohaeniyah; Muhammad, Farhana; Sholihah, Isfi; Hidayatul Aini, Siska (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The aims of this research were; 1) To find out where a cake merchant is in the midst of an online shop and 2) To find out what strategy the village wet cake merchants used in tackling the online shop competition. The study involves qualitative methods. The subject of research is the 10 people selling dump cake in the Village of Sikur. The data in this study is obtained through three methods, namel observation, interviews, and documentation. The data from this study was analyzed by reducing data, presenting data and drawing conclusions. The results of this study indicate that; 1) The state of the wet cake traders in the Sikur Village has a few decreased buyers caused by the presence of a new trade that is trading through online shop. The presence of this new trades system makes competition among traders stronger and plus also the progress of society that makes conventional trade begins to be abandoned. As a result of revenue most of the the wet cake traders in the Sikur Village decreased. 2) Most of the wet cake merchants in the Village of Sikur have a special defense strategy. The strategy used is product quality improvement strategies and promotional strategies.